Lumateperone for the Management of Bipolar Depression - Shajeeth J; Mohammed Sayeed Zaman K; Vijayakumar T M; N Sai Supra Siddhu (International Journal of Medical Toxicology and Legal Medicine, 2024)
Lumateperone is a new FDA-approved drug for the treatment of schizophrenia and depressive episodes ofbipolar I and II disorder. A literature review signifies that the lumateperone 42 mg once daily, administeredas a monotherapy or adjuvant therapy with lithium was helpful in managing the symptoms of schizophreniaand bipolar disorder. Clinical trials were used to evaluate the efficacy of lumateperone, by assessing theMontgomery- Aberg depression rating scale (MADRS) and clinical global impressions scale-bipolar versionseverity scale (CGI-BP-S). Safety assessment of lumateperone was assessed by adverse events andextrapyramidal symptoms. Extrapyramidal symptoms of lumateperone are low which is similar to that ofplacebo. According to the trials, this review concludes that the lumateperone 42mg was effective indepressive symptoms which are commonly associated with bipolar I and II disorder.